Method for introducing rare earth compound through cooperation of surface nanocrystallization and sol-gel
Through the surface nano-nanization synergistic sol gel method, the nanocrystal layer is formed on the surface of the matrix material and the introduction of rare earth compounds is solved, which hinders in-depth distribution of rare earth elements due to lattice distortion in chemical heat treatment, and achieves a more efficient penetration effect and surface strengthening of metal materials.
Patent Information
- Application Number
- CN202411761144.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-28
AI Technical Summary
During the chemical heat treatment process, rare earth elements cause lattice distortion due to the difference in the lattice radius from the matrix material, which hinders their in-depth distribution and fully exert their penetration effect.
The surface nano-normal synergistic sol-gel method is used to form a nanocrystalline layer on the surface of the matrix material, and rare earth compounds are introduced through the sol-gel layer, and the synergistic effect of the nanocrystalline layer and rare earth elements is used to promote the in-depth distribution of rare earth elements.
It significantly improves the penetration effect of rare earth elements in chemical heat treatment, increases the thickness and hardness of the modified layer, improves the surface strengthening effect of metal materials, and reduces energy losses.
Smart Images

Figure CN119530702A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material chemical heat treatment and surface engineering, and specifically is a method for introducing rare earth compounds by coordinating surface nano-crystallization with sol-gel. Background Art
[0002] As a key means of strengthening the surface of metal materials, chemical heat treatment is widely used in the field of modern material processing. In the complex process of chemical heat treatment, the diffusion behavior of active atoms is one of the core factors that determine the treatment effect.
[0003] In principle, there is a direct quantitative relationship between the diffusion depth of active atoms and the thickness of the surface modification layer. The increase in diffusion depth means that more active atoms are involved in the interaction with the base material, which in turn causes the thickness of the modified layer to increase continuously. This thickness change is closely related to the process time of chemical heat treatment. In traditional chemical heat treatment processes, in order to obtain the ideal thickness of the modified layer, it is often necessary to accurately control the process time. However, too long a process time will not only increase production costs, but may also cause damage to other material properties due to excessive processing, such as decreased toughness of the base material.
[0004] At the same time, the influence of active atom diffusion depth on the microstructure and mechanical properties of the modified layer is multifaceted. At the organizational level, different diffusion depths will cause changes in the rate of nucleation and growth direction, which in turn affects the size and morphology of the grains. For example, a deeper diffusion depth may lead to the formation of a finer and more uniform grain structure, because more active atoms provide a rich material basis for nucleation. In terms of mechanical properties, the hardness, wear resistance, and corrosion resistance of the modified layer are all related to the diffusion depth of active atoms. Properly increasing the diffusion depth can improve hardness and wear resistance, which is due to the formation of more complex chemical bonds and strengthening phases between the active atoms and the matrix atoms.
[0005] A large number of in-depth studies have confirmed that the introduction of rare earth elements in the chemical heat treatment process has great potential. Due to their special electronic structure and chemical properties, rare earth elements show unique advantages in promoting the diffusion of active atoms. As the chemical heat treatment process progresses, the presence of rare earth elements on the surface of the material can significantly change the diffusion dynamics of active atoms. Specifically, rare earth elements can reduce the activation energy of active atom diffusion, making it easier for active atoms to migrate inside the material. This promotion effect allows the chemical heat treatment rate to be increased, and deeper diffusion can be achieved in a shorter time, thereby increasing the thickness of the modified layer. Moreover, rare earth elements have a significant effect on improving the performance of the modified layer, not only improving hardness and wear resistance, but also enhancing special properties such as high temperature oxidation resistance. This is because rare earth elements can play a variety of positive roles in the modified layer, such as refining grains, purifying grain boundaries, and forming stable rare earth compounds.
[0006] However, rare earth elements face a key technical difficulty in their application. Due to the large difference in radius between rare earth atoms and metal atoms in the matrix, when rare earth atoms try to enter the matrix, strong lattice distortion will be induced. This lattice distortion is like an insurmountable obstacle, which greatly hinders the rare earth atoms from further penetrating into the matrix. From a microscopic point of view, lattice distortion changes the stress field and electron cloud distribution around the matrix atoms, so that rare earth atoms need to overcome higher energy barriers during migration. This phenomenon severely limits the catalytic effect of rare earth elements on deep areas inside the material, resulting in their inability to fully realize their potential. Therefore, how to achieve uniform and deep distribution of the introduced rare earth elements in the material, so as to comprehensively improve the catalytic effect, has become one of the important research topics that need to be solved in the current field of chemical heat treatment processing. The breakthrough of this topic is of vital significance to improving the quality of chemical heat treatment, expanding its scope of application, and promoting the development of surface strengthening technology of metal materials. Summary of the invention
[0007] The purpose of the present invention is to improve the catalytic effect of rare earth elements in chemical heat treatment, optimize the chemical heat treatment process, and enhance the surface strengthening effect of metal materials, thereby providing a method for introducing rare earth compounds by surface nano-coordinating sol-gel.
[0008] The method for introducing rare earth compounds by surface nano-crystallization and sol-gel synergistically is specifically carried out according to the following steps:
[0009] 1. Surface nano-crystalization of substrate materials: polishing and cleaning the surface of the substrate material, and using the surface nano-crystalization method to form a nano-crystal layer on the surface of the substrate material to obtain a substrate with surface nano-crystalization;
[0010] 2. Preparation of sol-gel layer: prepare sol-gel precursor solution by using rare earth source, complexing agent and reducing agent, mix well, dip-coat the sol-gel precursor solution on the surface of the nano-structured substrate material, and dry it in low temperature vacuum to obtain the pre-treated substrate material;
[0011] 3. Chemical heat treatment: Carburizing and heat treatment are performed on the pretreated matrix material in sequence, so as to complete the surface nano-crystallization and introduce rare earth compounds in coordination with sol-gel.
[0012] Beneficial effects of the present invention:
[0013] The present invention provides a method for introducing rare earth compounds through surface nano-sizing and sol-gel catalytic pretreatment and its application. The carburizing efficiency of the material treated by the method of the present invention is significantly improved, the thickness of the carburized layer is increased, and the hardness and wear resistance are significantly improved. While improving the structure and mechanical properties of the carburized layer, energy loss can be reduced.
[0014] The thickness of the modified layer using the method of the present invention is increased compared with the modified layer thickness of the sample without pretreatment, the number of sub-surface carbides is larger and the size distribution is more uniform, further improving the mechanical properties of the modified layer; after the nanocrystalline layer is formed on the surface, the small-sized grains and a large number of defects formed make it easier for the rare earth elements in the rare earth compound sol-gel to enter the interior of the matrix, thereby enhancing the catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is the basic vacuum carburizing process diagram in Example 1 and Example 2;
[0016] Figure 2 The process flow and modified layer schematic diagram of Example 1;
[0017] Figure 3 This is a scanning electron microscope image of carbides on the top of the carburized modified layer of the composite pretreated sample in Example 1;
[0018] Figure 4 This is a bar graph of the diameter distribution of metal atoms of carbides at the top of the carburized modified layer of the composite pretreated sample of Example 1;
[0019] Figure 5 This is a scanning electron microscope image of carbides on the top of the carburized modified layer of the sample without pretreatment in Example 2;
[0020] Figure 6 This is a bar chart showing the distribution of carbide metal atom diameters at the top of the carburized modified layer of the sample in Example 2 without pretreatment. DETAILED DESCRIPTION
[0021] Specific implementation method 1: In this implementation method, a method for introducing rare earth compounds by surface nano-crystallization and sol-gel is specifically carried out according to the following steps:
[0022] 1. Surface nano-crystalization of substrate materials: polishing and cleaning the surface of the substrate material, and using the surface nano-crystalization method to form a nano-crystal layer on the surface of the substrate material to obtain a substrate with surface nano-crystalization;
[0023] 2. Preparation of sol-gel layer: prepare sol-gel precursor solution by using rare earth source, complexing agent and reducing agent, mix well, dip-coat the sol-gel precursor solution on the surface of the nano-structured substrate material, and dry it in low temperature vacuum to obtain the pre-treated substrate material;
[0024] 3. Chemical heat treatment: Carburizing and heat treatment are performed on the pretreated matrix material in sequence, so as to complete the surface nano-crystallization and introduce rare earth compounds in coordination with sol-gel.
[0025] The present invention proposes a method for introducing rare earth compounds through surface nano-processing in coordination with sol-gel and its catalytic infiltration pretreatment application, combines surface nano-processing technology with the technology of introducing rare earth compounds through sol-gel, utilizes the fine grain structure formed on the surface of the material by surface nano-processing to provide more diffusion channels for active atoms, and simultaneously utilizes the rare earth compound sol layer to form nano-oxide particles on the surface of the material to accelerate atomic diffusion, and uses the refined grains to penetrate into the matrix to improve the carburizing rate, thereby achieving efficient catalytic infiltration.
[0026] After the surface of the substrate material is nano-processed in this embodiment, a nanocrystalline layer is formed on the surface. The nanocrystalline layer has a high specific surface area, and the increase in specific surface area provides more sites for the subsequent adsorption and diffusion of rare earth elements. In addition, the grain boundary density of the nanocrystalline layer is high. During the chemical heat treatment process, the rare earth elements can diffuse more quickly into the substrate through these grain boundary channels, thereby improving the catalytic effect of the rare earth elements in the chemical heat treatment.
[0027] In this embodiment, when the sol-gel precursor solution is dip-coated on the surface of the substrate material with nano-surface, the rare earth elements can be evenly covered on the substrate surface due to the fluidity and wettability of the solution. Compared with the traditional rare earth addition method, the sol-gel method can better control the content and distribution of rare earth elements. After drying in a low-temperature vacuum, the formed gel layer can effectively fix the rare earth elements to prevent them from agglomerating or losing in the subsequent treatment process, thereby ensuring that the rare earth elements can continue to play their catalytic role in the chemical heat treatment process.
[0028] In the carburizing process of this embodiment, the nanocrystalline layer on the surface of the substrate material with surface nanonization and the evenly distributed rare earth elements work synergistically. The rare earth elements can reduce the adsorption energy of carbon on the substrate surface, making it easier for carbon to be adsorbed on the substrate surface. At the same time, the presence of the nanocrystalline layer accelerates the diffusion channel of carbon, allowing carbon to diffuse faster into the substrate. The heat treatment process further optimizes the distribution of rare earth elements and the organizational structure of the substrate material. During the heat treatment process, the rare earth elements can inhibit the growth of grains in the substrate material and refine the grain structure. This not only improves the strength of the substrate material, but also makes the distribution of rare earth elements in the substrate material more stable, thereby improving the surface strengthening effect of the metal material.
[0029] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the base material in step 1 is steel. The rest is the same as the specific implementation method 1.
[0030] Specific implementation method 3: This implementation method is different from the specific implementation method 2 in that the base material is a cubic block of 12mm*12mm*12mm. Other aspects are the same as the specific implementation method 2.
[0031] Specific embodiment 4: This embodiment is different from specific embodiment 1 in that the cleaning in step 1 is performed by using ultrasonic waves in an acetone solution. The rest is the same as specific embodiment 1.
[0032] Specific embodiment 5: This embodiment differs from specific embodiment 1 in that the surface nano-crystallization method in step 1 is a mechanical method, a chemical method or a heat treatment method. The rest is the same as specific embodiment 1.
[0033] Specific embodiment 6: This embodiment differs from specific embodiment 1 in that: in step 1, supersonic particle bombardment is used to perform surface nano-crystallization. The rest is the same as specific embodiment 1.
[0034] Specific embodiment 7: This embodiment is different from specific embodiment 6 in that the particles in the supersonic particle bombardment are aluminum oxide particles with a diameter of 40 to 60 μm, the nozzle pressure is 2.0 MPa, the particles are accelerated to 300 to 1200 m / s to bombard the surface, the bombardment distance is 20 mm, and the bombardment time is 200 to 360 s. Others are the same as specific embodiment 6.
[0035] Specific embodiment eight: This embodiment differs from specific embodiment one in that the use of rare earth source, complexing agent and reducing agent to prepare sol-gel precursor solution in step two is specifically carried out in the following steps: Fe(NO3)3·9H2O, La(NO3)3·6H2O and citric acid are dissolved in ethylene glycol solution to prepare 0.4 mol / L LaFeO3 sol-gel precursor solution, and stirred at room temperature for 3 hours. The rest is the same as specific embodiment one.
[0036] Specific embodiment 9: This embodiment is different from specific embodiment 1 in that the carburizing treatment in step 3 is a pulse cycle carburizing treatment at 900°C, the carbon source is acetylene gas, and 25 pulse cycles are performed during the carburizing cycle. Other aspects are the same as specific embodiment 1.
[0037] Specific embodiment 10: This embodiment differs from specific embodiment 1 in that the heat treatment in step 3 is annealing at 650° C., oil quenching at 810° C., and low-temperature tempering at 150° C. The rest is the same as specific embodiment 1.
[0038] The beneficial effects of the present invention are verified by the following examples:
[0039] Example 1: A method for introducing rare earth compounds by surface nanostructured sol-gel is specifically carried out according to the following steps:
[0040] 1. Surface nano-crystallization of substrate material: steel is cut into cubic blocks of 12mm*12mm*12mm, cleaned in acetone solution by ultrasonic wave after polishing, and surface nano-crystallization is performed by supersonic particle bombardment to obtain a substrate with surface nano-crystallization; the particles in the supersonic particle bombardment are aluminum oxide particles with a diameter of 40 to 60 μm, the nozzle pressure is 2.0 MPa, the particles are accelerated to 300 to 1200 m / s to bombard the surface, the bombardment distance is 20 mm, and the bombardment time is 200 to 360 s;
[0041] 2. Preparation of sol-gel layer: Fe(NO3)3·9H2O, La(NO3)3·6H2O and citric acid were dissolved in ethylene glycol solution to prepare 0.4 mol / L LaFeO3 sol-gel precursor solution, wherein Fe(NO3)3·9H2O was used as Fe source, La(NO3)3·6H2O was used as La source, citric acid was used as complexing agent, and ethylene glycol was used to reduce perovskite crystal particles and improve the uniformity of particle distribution. The solution was stirred at room temperature for 3 h to promote the complexing reaction. After being mixed evenly, the sol-gel precursor solution was dip-coated on the surface of the substrate material with nano-surface, and dried in low-temperature vacuum to obtain the pretreated substrate material.
[0042] 3. Chemical heat treatment: The pretreated matrix material is subjected to pulse cycle carburizing treatment at 900°C, with acetylene gas as the carbon source, and 25 pulse cycles are performed during the carburizing period; then annealing treatment is performed at 650°C, oil quenching treatment is performed at 810°C, and low-temperature tempering treatment is performed at 150°C. After the above treatment method is used, a carburizing modification layer is formed on the surface of the composite pretreated sample, that is, the surface nano-crystallization and sol-gel synergistic introduction of rare earth compounds are completed.
[0043] Example 2: Ordinary vacuum carburizing The specific implementation steps are as follows:
[0044] 1. Nano-crystallization of the substrate surface: Cut the steel into 12mm*12mm*12mm cubic blocks, polish them, and then clean them in an acetone solution using ultrasound to obtain the pre-treated substrate material;
[0045] 2. Chemical heat treatment: The pretreated base material is subjected to pulse cycle carburizing treatment at 900°C, with acetylene gas as the carbon source, and 25 pulse cycles are performed during the carburizing cycle; then annealing treatment is performed at 650°C, oil quenching treatment is performed at 810°C, and low-temperature tempering treatment is performed at 150°C. After the above treatment method is used, a carburized modified layer is formed on the surface of the composite pretreated sample.
[0046] Figure 3 , Figure 4 The carbide characteristics on the top of the carburized modified layer of the composite pre-treated sample are shown. Figure 5 , Figure 6This is a sample without pretreatment and carburization. Compared with the sample without pretreatment, the number of carbides in the composite layer sample increased slightly and the size increased, but the carbide size after the increase is still the optimal carbide size.
Claims
1. A method for introducing rare earth compounds by surface nano-crystallization and sol-gel, characterized in that The method for introducing rare earth compounds by surface nano-crystallization and sol-gel is specifically carried out according to the following steps:
1. Surface nano-crystalization of substrate materials: polishing and cleaning the surface of the substrate material, and using the surface nano-crystalization method to form a nano-crystal layer on the surface of the substrate material to obtain a substrate with surface nano-crystalization; 2. Preparation of sol-gel layer: prepare sol-gel precursor solution by using rare earth source, complexing agent and reducing agent, mix well, dip-coat the sol-gel precursor solution on the surface of the nano-structured substrate material, and dry it in low temperature vacuum to obtain the pre-treated substrate material; 3. Chemical heat treatment: Carburizing and heat treatment are performed on the pretreated matrix material in sequence, so as to complete the surface nano-crystallization and introduce rare earth compounds in coordination with sol-gel.
2. The method for introducing rare earth compounds by surface nano-crystallization and sol-gel according to claim 1, characterized in that The base material in step 1 is steel.
3. The method for introducing rare earth compounds by surface nano-crystallization and sol-gel according to claim 2, characterized in that The base material is a cubic block of 12mm*12mm*12mm.
4. The method for introducing rare earth compounds by surface nano-crystallization and sol-gel according to claim 1, characterized in that The cleaning in step 1 is performed by using ultrasonic waves in an acetone solution.
5. The method for introducing rare earth compounds by surface nano-crystallization and sol-gel according to claim 1, characterized in that The surface nano-crystallization method in step 1 is a mechanical method, a chemical method or a heat treatment method.
6. The method for introducing rare earth compounds by surface nano-crystallization and sol-gel according to claim 1, characterized in that In step 1, supersonic particle bombardment is used to perform surface nano-crystallization.
7. The method for introducing rare earth compounds by surface nano-crystallization and sol-gel according to claim 6, characterized in that In the supersonic particle bombardment, the particles are aluminum oxide particles with a diameter of 40 to 60 μm, the nozzle pressure is 2.0 MPa, the particles are accelerated to 300 to 1200 m / s to bombard the surface, the bombardment distance is 20 mm, and the bombardment time is 200 to 360 s.
8. The method of introducing rare earth compounds by surface nano-crystallization and sol-gel according to claim 1, characterized in that The preparation of the sol-gel precursor solution using a rare earth source, a complexing agent and a reducing agent as described in step 2 is specifically carried out according to the following steps: dissolve Fe(NO3)3·9H2O, La(NO3)3·6H2O and citric acid in ethylene glycol solution to prepare a 0.4 mol / LLaFeO3 sol-gel precursor solution, and stir at room temperature for 3 hours.
9. The method of introducing rare earth compounds by surface nano-crystallization and sol-gel according to claim 1, characterized in that The carburizing treatment in step 3 is a pulse cycle carburizing treatment at 900° C., the carbon source is acetylene gas, and 25 pulse cycles are performed during the carburizing cycle.
10. The method for introducing rare earth compounds by surface nano-crystallization and sol-gel according to claim 1, characterized in that The heat treatment in step 3 is annealing at 650°C, oil quenching at 810°C, and low-temperature tempering at 150°C.
Citation Information
Patent Citations
Surface nanocrystallization method capable of accelerating vacuum carburizing rate
CN108179374A
Alloy steel vacuum carburizing pretreatment method, vacuum carburizing method and alloy steel
CN110172647A
Rapid low-pressure gas nitriding method
CN110747430A
Method for accelerating plasma nitriding with assistance of rare earth compound
CN113136539A
Manufacture method of natural stone patterned texture layer custom block
KR1020210108839A